Antibacterial activity and in situ efficacy of Bidens pilosa Linn and Dichrostachys cinerea Wight et Arn extracts against common diarrhoea-causing waterborne bacteria - Pfarelo Daphney Shandukani; Shonisani Cathphonia Tshidino; Peter Masoko; Kgabo Maureen Moganedi (BMC, 2018)
Abstract Background Bidens pilosa and Dichrostachys cinerea extracts were investigated for the antibacterial properties against waterborne diarrhoeagenic bacteria. Methods The plant materials were extracted using the direct and serial exhaustive methods using solvents of varying polarities, namely, hexane, dichloromethane, ethyl acetate, acetone and methanol. Qualitative phytochemical analysis and quantitative determination of total phenolic content of the leaf powders of the two plants were tested. The antioxidant activities of the plants were determined using the 2, 2-diphenyl-1-picrylhydrazyl method. The toxic effect of the extracts on C2C12 muscle cell line were assessed by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide method and the antibacterial activity was determined using the serial microbroth dilution. Results Methanol leaf extracts both plants had the highest yield in both direct and serial exhaustive extraction methods. Phytochemical profiling of the extracts displayed the presence of various secondary metabolites. The Benzene: ethanol: ammonia hydroxide solvent system showed a good resolution of chemical compounds in plant extracts from both plants. Most antioxidant compounds observed were developed in chloroform: ethyl acetate: formic acid and ethyl acetate: methanol: water solvent systems. All the bacterial species tested were sensitive to the effect of different extracts of both plant species, with E. coli being less sensitive to the effect of the extracts from D. cinerea. Following the simulated gastric fluid (SGF) treatment, a decrease in the antibacterial potency of the extracts was observed. No extract was toxic to the C2C12 muscle cell line. Conclusion The presence of the secondary metabolites and nontoxic effect of the two plants tested may affirm the medicinal value of these leaf extracts. Our results suggest that B. pilosa and D. cinerea contain constituents with antioxidant and antimicrobial activities, which could be used in the treatment of diarrhoea in a case where untreated surface water is used.